Step * 1 1 of Lemma ftc-integral


1. Interval
2. iproper(I)
3. {a:ℝa ∈ I} 
4. ∀f:{f:I ⟶ℝ| ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((f x) (f y)))} . ∀g:I ⟶ℝ.
     (d(g[x])/dx = λx.f[x] on  (∃c:ℝ. ∀x:{a:ℝa ∈ I} (a_∫-f[t] dt (g[x] c))))
5. {a:ℝa ∈ I} 
6. {f:I ⟶ℝ| ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((f x) (f y)))} 
7. I ⟶ℝ
8. d(g[x])/dx = λx.f[x] on I
9. : ℝ
10. ∀x:{a:ℝa ∈ I} (a_∫-f[t] dt (g[x] c))
11. ∀a,b:{a:ℝa ∈ I} .  (a_∫-f[t] dt ∈ ℝ)
⊢ a_∫-f[t] dt (g[b] g[a])
BY
((InstHyp [⌜a⌝(-2)⋅ THENA Auto) THEN (InstHyp [⌜b⌝(-3)⋅ THENA Auto)) }

1
1. Interval
2. iproper(I)
3. {a:ℝa ∈ I} 
4. ∀f:{f:I ⟶ℝ| ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((f x) (f y)))} . ∀g:I ⟶ℝ.
     (d(g[x])/dx = λx.f[x] on  (∃c:ℝ. ∀x:{a:ℝa ∈ I} (a_∫-f[t] dt (g[x] c))))
5. {a:ℝa ∈ I} 
6. {f:I ⟶ℝ| ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((f x) (f y)))} 
7. I ⟶ℝ
8. d(g[x])/dx = λx.f[x] on I
9. : ℝ
10. ∀x:{a:ℝa ∈ I} (a_∫-f[t] dt (g[x] c))
11. ∀a,b:{a:ℝa ∈ I} .  (a_∫-f[t] dt ∈ ℝ)
12. a_∫-f[t] dt (g[a] c)
13. a_∫-f[t] dt (g[b] c)
⊢ a_∫-f[t] dt (g[b] g[a])


Latex:


Latex:

1.  I  :  Interval
2.  iproper(I)
3.  a  :  \{a:\mBbbR{}|  a  \mmember{}  I\} 
4.  \mforall{}f:\{f:I  {}\mrightarrow{}\mBbbR{}|  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((f  x)  =  (f  y)))\}  .  \mforall{}g:I  {}\mrightarrow{}\mBbbR{}.
          (d(g[x])/dx  =  \mlambda{}x.f[x]  on  I  {}\mRightarrow{}  (\mexists{}c:\mBbbR{}.  \mforall{}x:\{a:\mBbbR{}|  a  \mmember{}  I\}  .  (a\_\mint{}\msupminus{}x  f[t]  dt  =  (g[x]  +  c))))
5.  b  :  \{a:\mBbbR{}|  a  \mmember{}  I\} 
6.  f  :  \{f:I  {}\mrightarrow{}\mBbbR{}|  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((f  x)  =  (f  y)))\} 
7.  g  :  I  {}\mrightarrow{}\mBbbR{}
8.  d(g[x])/dx  =  \mlambda{}x.f[x]  on  I
9.  c  :  \mBbbR{}
10.  \mforall{}x:\{a:\mBbbR{}|  a  \mmember{}  I\}  .  (a\_\mint{}\msupminus{}x  f[t]  dt  =  (g[x]  +  c))
11.  \mforall{}a,b:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    (a\_\mint{}\msupminus{}b  f[t]  dt  \mmember{}  \mBbbR{})
\mvdash{}  a\_\mint{}\msupminus{}b  f[t]  dt  =  (g[b]  -  g[a])


By


Latex:
((InstHyp  [\mkleeneopen{}a\mkleeneclose{}]  (-2)\mcdot{}  THENA  Auto)  THEN  (InstHyp  [\mkleeneopen{}b\mkleeneclose{}]  (-3)\mcdot{}  THENA  Auto))




Home Index